Impact of adrenalectomy and dexamethasone treatment on testicular morphology and sperm parameters in rats: insights into the adrenal control of male reproduction - Silva, E. J. R.; Vendramini, V.; Restelli, A.; Bertolla, R. P.; Kempinas, W. G. [UNESP]; Avellar, M. C. W. (Wiley-Blackwell, 2014)
Here we investigated the hypothesis that normal levels of glucocorticoids, a class of adrenal steroid hormones, are required for normal testicular and epididymal functions. We examined the effects of the manipulation of glucocorticoid plasma levels by bilateral adrenalectomy (1, 2, 7 and 15days) alone or in combination with daily treatment with the synthetic glucocorticoid dexamethasone (DEX; 5g/kg, i.p., 6days) on the morphology of the testis and sperm parameters in rats. We showed that adrenalectomy led to a reduction in testicular sperm count and daily sperm production starting 2days after surgery and a differential decrease in sperm count in the epididymis, according to the region and time post-adrenalectomy analysed. In parallel, testes from 7-day adrenalectomized (ADX) rats displayed a higher frequency of damaged seminiferous tubules and the presence of elongated spermatids retained in the basal epithelial compartment in stages IX-XVII, which is indicative of defective spermiation. The alkaline comet assay revealed a late effect of adrenalectomy on epididymal sperm DNA fragmentation, which was increased only 15days after surgery. DEX treatment prevented the changes in testicular and epididymal sperm count observed in 7-day ADX rats, but failed to protect the testis from ADX-induced morphological abnormalities. Thus, our results indicated that glucocorticoids may be involved in events related to the maintenance of spermatogenesis and sperm maturation during adulthood. These findings provide new insights into the importance of adrenal steroids to male fertility.
Keywords: adrenalectomy; animal models; epididymis; hormones; rat; sperm quality parameters; testis